The Evolution Of Symbolic Communication Into Comprehensive Writing Systems - Qambaraliyeva Robiyaxon Akmal qizi; Djumaboyeva Mokhira Anvarovna (Academia One Publishing, 2025)
The article explores the development of symbolic communication into full-fledged writing systems, from primitive signs to modern alphabets. Key stages of writing development in different cultures, including Mesopotamia, Egypt, China and MesoAmerica are considered. It analyzes the prerequisites of the origin of the letter, its function and influence on the development of human civilization
Keywords: Symbolic communication; pictogram; ideogram